2018
DOI: 10.1073/pnas.1805062115
|View full text |Cite
|
Sign up to set email alerts
|

Generating carbon schwarzites via zeolite-templating

Abstract: SignificanceNanocarbons can be characterized by their curvature—that is, positively curved fullerenes, zero-curved graphene, and negatively curved schwarzites. Schwartzites are fascinating materials but have not been synthesized yet, although disordered materials with local properties similar to schwarzites (“random schwarzites”) have been isolated. A promising synthetic method allows for the interior surfaces of zeolites to be templated with normalsnormalp2 carbon, but theoretical study of these zeolite-templ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
122
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 103 publications
(127 citation statements)
references
References 68 publications
3
122
0
Order By: Relevance
“…It has been recently reported that the growth of carbon inside the hard porous materials, so-called template carbonization (Kyotani et al, 1997), has successfully synthesized carbons with structures that fits the description of schwarzites (Braun et al, 2018). Zeolite Y (FAU) is a commonly used template material, due to its three-dimensional pore structure, high thermal stability, and large pores (Kyotani et al, 2003;Braun et al, 2018).…”
Section: Introductionmentioning
confidence: 99%
“…It has been recently reported that the growth of carbon inside the hard porous materials, so-called template carbonization (Kyotani et al, 1997), has successfully synthesized carbons with structures that fits the description of schwarzites (Braun et al, 2018). Zeolite Y (FAU) is a commonly used template material, due to its three-dimensional pore structure, high thermal stability, and large pores (Kyotani et al, 2003;Braun et al, 2018).…”
Section: Introductionmentioning
confidence: 99%
“…Considering the results presented in Table 3, schwarzites can be considered extremely attractive for any application in which lightweight yet highly energy absorbent materials are needed, such as body armor. There have been important synthesis advances for schwarzites inside zeolites [11,13,61], and large-size structures could be a reality in the coming years. Also, a recently 3D printed version of atomic schwarzite models was reported [42] and surprisingly some of their mechanical properties proved to be scale-independent.…”
Section: Resultsmentioning
confidence: 99%
“…Other works investigated the stability of some schwarzite structures [7][8][9][10] and possible synthesis routes [11][12][13][14]. Although the complex geometry of schwarzites poses significant challenges for their synthesis, they have been used to model realistic synthesized carbon nanofoams [15][16][17][18][19] and to clarify the role of negative Gaussian curvature in chemical structures [20] and biophysical systems [21,22].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…These stipulations preclude solubility‐enhancing substituents and heteroatom directing groups to aid C−C bond forming reactions. These latter targets are especially appealing, however, as they can be viewed as subunits of new carbon allotropes extending in three dimensions (i.e., “Schwarzites”, or “Mackay crystals”) …”
Section: Methodsmentioning
confidence: 99%